Meta-Analysis the Effect of Excessively Loud Sounds on Noise Induced Hearing Loss in Manufacturing Industry Workers - Rizki Aqsyari; Sumardiyono Sumardiyono; Bhisma Murti (Masters Program in Public Health, 2023)
Background: Noise that exceeds the threshold value can cause work-related illness, which can be in the form of hearing loss or damage to the ear either temporarily or permanently after being exposed for a certain period of time without adequate protection. Noise-induced hearing loss (NIHL) is a working condition that often occurs in various industrial spectrums. This study aims to estimate the magnitude of the effect of noise on NIHL in manufacturing industry workers.Subjects and Method: This research is a systematic review and meta-analysis. Article search was carried out based on the PICO Model eligibility criteria including: P= Manufacturing industry worker; I= Noise intensity ≥85 dB; C= Noise intensity <85 dB; O= NIHL. The articles used come from 3 databases, namely: PubMed, Google Scholar, and Science Direct. The keywords used include “hearing loss” AND “noise-induced hearing loss” AND “manufacturing industry” AND “cross-sectional study”. The inclusion criteria in this study included full-text articles with a cross-sectional study design, the adjusted odds ratio (aOR) was used, the articles were published in the 2003-2022 range, and the outcome was NIHL. Articles were analyzed using the PRISMA diagram and the Review Manager 5.3 application.Results: A meta-analysis of 10 articles from Arab Saudi, Ethiopia, Kuwait, Tanzania, Thailand, Cina, Yordania, Norwegia, and Iran showed that ≥85 dB noise increases the likelihood of NIHL in industrial manufacturing workers. Manufacturing workers exposed to noise intensity of ≥85 dB increased NIHL by 1.90 times compared to manufacturing workers exposed to <85 dB of noise, and this result was statistically significant (aOR= 1.90; CI 95%= 1.61 to 2.26; p< 0.001).Conclusion: A meta-analysis of 10 cross-sectional studies concluded that noise increases the incidence of NIHL in manufacturing industry workers. Keywords: noise intensity, NIHL, manufacturing industry workers Correspondence: Rizki Aqsyari. Master’s Program in Public Health, Master’s Program, Universitas Sebelas Maret. Jl ir sutami no 36A Jebres, Surakarta. Email: Rizkiaqsyarid@gmail.com. Mobile: +6281272778423.